Hyperprolactinemia during application of second-generation antipsychotics: the principles of prevention, diagnosis and correction - L. N. Gorobets; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article presents compelling evidence of the need to draw attention of physicians to the problem of neyroleptical hyperprolactinemia. The article provides information about different prolactogen activity of antipsychotics with the release of the safest drugs - aripiprazole and ziprasidone. Substantiates the necessity of correction prolactin levels during antipsychotic therapy. Presented the algorithms for the prevention and monitoring of neuroleptic hyperprolactinemia, as well as the basic principles of its correction, including with the use of a dopamine agonist Dostinex.